INFLUENCE OF LEES PRESENCE DURING THE RESTING TIME OF BASE WINE IN SOME VOLATILE COMPOUNDS OF PERUVIAN ITALIA GRAPE PISCO - Hidalgo, Yasser (2016)
The influence of lees presence during the resting time of base wines in some volatile compounds in Pisco obtained therefrom were studied, such as: acetic acid, higher alcohols, esters and acetaldehyde. Two dry base wine fractions (with and without lees) were stored for five time intervals: 0, 7, 20, 60, 150 days, and distilled afterwards. The results indicated that piscos obtained from base wines with longer resting time show higher acetic acid contents (with lees: from 0.15 g/L with 0 resting days to 0.30 g/L with 60 resting days and 0.69 g/L with 150 resting days; without lees: from 0.14 g/L with 0 resting days to 0.26 g/L with 150 resting days), propanol contents (with lees: from 72.15 mg/100 mL A.A. with 0 resting days to 105.34 mg/100 mL A.A. with 150 resting days), ethyl acetate contents (with lees: from 22.00 mg/100 mL A.A. with 0 resting days to 43.10 mg/100 mL A.A. with 150 resting days) and iso-amyl acetate contents (with lees: from 0.00 mg/100 mL A.A. with 0 resting days to 10.57 mg/100 mL A.A. with 150 resting days); and lower acetaldehyde contents (with lees: from 22.71 mg/100 mL A.A. with 0 resting days to 4.29 mg/100 mL A.A. with 60 resting days and 3.30 mg/100 mL A.A. with 150 resting days; without lees: from 16.98 mg/100 mL A.A. with 0 resting days to 4.30 mg/100 mL A.A. with 150 resting days). Piscos coming from base wines with lees show higher ethyl acetate (22.00 vs. 16.61 mg/100 mL A.A.) and acetaldehyde (22.71 vs. 16.98 mg/100 mL A.A.) contents than those coming from base wines without lees, with 0 resting days.